Representações sobre ser plurilíngue em escolas monolíngues de fronteira - Juliani, Elaine Manoel (2021)
Postmodern relations have produced studies and reflections on the themes “plurilinguism”, “hybridism”, “identity” “culture”, among others, and, when it comes to borders, they become even more pertinent. Past events such as the “War of the Triple Alliance” and other political decisions contributed to the construction of relations between Brazil, Paraguay and Argentina. Thus, in the frontier discourses it is possible to find essentialisms (that is, the search for homogeneity), represented by stereotypes and perpetuated through narratives that seek to determine identities. The interaction through the speeches takes place mainly in the classroom, where the time spent together is longer and restricted to the same environment, therefore, paying attention to what is being said there is of fundamental importance. With the percep tion of the predominance of monolingual thinking in border classrooms, discussions that deal with representations of being multilingual in this context become relevant and latent. Approaching these aspects and using qualitative / interpretive research as a methodology combined with ethnography, the general objective of this research is to verify how identity representations about being plurilingual in monolingual frontier school environments are constructed. In addition, by also making a survey of the researches carried out on the linguistic plurality of the West of Paraná, mainly on the Brazil/Paraguay/Argentina border, focusing on the school context, and identifying, in the discursive practices of elementary and high school teachers in Foz do Iguaçu, as identity representations about being a multilingual student are constructed in the monolingual context of the classroom, we will bring discussions inside and outside the school, making perceptions about the other more fluid, allowing the construction of new knowledge and discourses.